Analisis Terhadap Dissenting Opinion Dalam Penyelesaian Sengketa Kepailitan Di Indonesia - Chairunnnisa, Amanda; Bachtiar, Maryati; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The settlement of a civil case one of the duties of a judge is to investigate whether the legal relationshipthat is the basis of the claim really exists or not. For this reason, the judge must know objectively the truth ofthe event through proof. The conditions for submitting a bankruptcy application to the commercial court arevery important because if the bankruptcy application does not meet the conditions contained in the PKPUBankruptcy Act, the commercial court will not grant the bankruptcy application. However, in this studybankruptcy problems occurred which were not in accordance with the Act which was granted bankruptcy by PTAndalan Artha Advisido (AAA Securities). Therefore the purpose of this Thesis Writing, namely: first, To findout the factors that led to the emergence of dissenting opinions in the settlement of bankruptcy disputes inIndonesia. Second, to find out an analysis of bankruptcy disputes in Indonesia in the event of a dissentingopinion.This type of research can be classified in the type of normative juridical research research, whichexamines the principles of law, precisely the principles of jurisprudence and the resolution of disputesconcerning the matter of justice in state practice. In this type of legal research, law is often conceptualized aswhat is written in the laws and regulations (law in books) or the law conceptualized as a norm or norm which isa standard of human behavior that is deemed appropriate. Data sources are used, namely: primary data,secondary and tertiary data.The conclusion that can be obtained from the results of the first research, Dissenting opinion inbankruptcy cases in general is due to the judge's freedom in deciding cases that are limited by the provisions ofthe legislation. Whereas in particular the emergence of dissenting opinions in bankruptcy cases is due todifferences in the background of judges examining the bankruptcy case, namely the existence of career judgesand ad-hoc judges. Second, the bankruptcy case of PT. AAA Securities is seen as a mistake, whether committedby the bankruptcy applicant or the Panel of Judges. The bankrupt applicant submits an application for abankruptcy statement against PT. AAA Securities to the Central Jakarta Commercial Court without goingthrough the Financial Services Authority as the authorized party. And the Panel of Judges does not consider theprovisions of Article 2 paragraph (4) of the Bankruptcy and PKPU Law. Based on these provisions, thebankruptcy petitioner should not be authorized to submit an application for bankruptcy to the bankruptcyrespondent, but the authorized party to file a bankruptcy petition against the bankruptcy respondent is only theFinancial Services Authority.